The moderating effect of olfactory function on the relationship between interpersonal problems and the emotional intelligence of adults - Lee, Won-Jin; Kim, Sun-Hee; Cha, Hye-Gyeong (Edelweiss Applied Science and Technology, 2025)
This study examined the relationships among emotional intelligence, olfactory function, and interpersonal problems, as well as the moderating role of olfactory function. A total of 119 adults aged 18 and older were recruited from a university in Region C, South Korea, between December 1 and 22, 2023. Participants completed standardized surveys and tests. Data were analyzed using SPSS 29.0 and Hayes’ PROCESS macro 4.2, employing descriptive statistics, t-tests, ANOVA, Pearson correlation, hierarchical regression, and simple slope analysis. Results showed that interpersonal problems were negatively correlated with both emotional intelligence (r = -0.46, p < .001) and olfactory function (r = -0.21, p < .05). Olfactory function significantly moderated the relationship between emotional intelligence and interpersonal problems (F = 5.512, p < .001), with an adjusted R² of 34.9%. Simple slope tests indicated that higher emotional intelligence was linked to fewer interpersonal problems across all levels of olfactory function, with stronger effects in those with average or high olfactory ability. These findings suggest that interventions aimed at improving emotional intelligence and olfactory function may be effective in reducing interpersonal difficulties.